Effect of strain rate on the mechanical properties of polycarbonate processed by compression and injection molding. Issue 1 (4th November 2021) - Ullrich, Fabian; Singh, Shailendra Pal Veer; McDonald, Sean; Krueger, Alex; Vera‐Sorroche, Javier; Amirkhizi, Alireza; Masato, Davide
Abstract: The high impact strength of polycarbonate has been studied and exploited for many applications. However, the interaction between processing‐induced effects and the strain rate affects the mechanical behavior significantly. In this work, the effects of the processing‐induced thermal history, generated by either injection molding or compression molding, were characterized. Polycarbonate samples manufactured with the two processes were experimentally compared using quasi‐static and dynamic compression testing. The processing effects are further evaluated by combining a numerical calculation of the temperature history and a constitutive model to predict the yield strength of the glassy polymer. The constitutive modeling approach considers both the effect of the rate‐dependent and stress‐activated motion of the chain segments, and the strain‐hardening effect due to molecular alignment. The results indicate that the thermal history has a significant effect at low strain rates, while its influence is negligible in the dynamic range. The modeling effort allows estimating the yield strength with different accuracy depending on the strain rate values. Abstract : Effect of molding‐induced thermal history on the high‐strain rate compression properties of polycarbonate.